The Relationship Between Social Support and Disturbance Anxiety in Men in Same-Sex Relationships - Suwini Tasik Minanga; Andi Asrina; Sumiaty Sumiaty; Yusriani Yusriani; Fairus Prihatin Idris; Fatmah Afrianty Gobel (An Idea Health Journal, 2026)
Introduction: Mental health is an important aspect for men in same sex Relationship population in facing complex psychosocial challenges, including trauma, stigma, and discrimination. Social support is believed to play a protective role in reducing anxiety. And the lack of support from family, friends, and staff compared to Peer Support Groups (PSG) may be caused by the lack of openness of PLHIV regarding HIV status. Many PLHIV choose not to disclose their condition to family or friends because of concerns about stigma and discrimination that are still strong in the family and community environment. Fear of rejection, or different treatment, makes PLHIV tend to close themselves and seek support from PSGs who are considered to have a better understanding of PLHIV's condition. In PSGs, PLHIV feel more accepted, understood, and not judged, so emotional support and motivation are easier to obtain than from families who may not be openly accepting. This study aims to analyze the relationship between peer support groups and anxiety disorders in men in same sex Relationship population in Bulukumba Regency. Quantitative research with a cross-sectional approach. The researchsample was taken using an accidental sampling technique from the men in same sex Relationship population. Showed that peer support groups (PSGs) were proven to have a significant relationship with anxiety, p = 0.001, and were the most relevant factors in increasing anxiety in the men in same sex Relationship population. This study is that PSGs have a central role in supporting anxiety in men in same sex Relationship risk populations. These findings emphasize the importance of strengthening peer support group programs through counseling, education, and emotional support to reduce anxiety, depression, and the impact of social stigma.